Bioequivalence Study of Fixed Dose Combination of Atorvastatin and Ezetimibe Tablet in Healthy Volunteers by LC-MS/MS Method - VEERAN GOWDA, K.; SENTHIL RAJAN, D.; MANDAL, U.; SAM SOLOMON, W.D.; SENTHAMIL SELVAN, P.; BOSE, A.; SARKAR, A.K.; CHATTARAJ, T.K.; PAL, T.K. (Asian Journal of Chemistry, 2010)
This study presents the results of two period, two treatment, cross-over investigations on 12 healthy male volunteers to assess the bioequivalence of two fixed dose combination (FDC) products of two manufacturers containing atorvastatin 10 mg and ezetimibe 10 mg. The two products tested were capsule Zetitor-10 (Caplin Point Laboratories Ltd., Pondichery, India) as a reference product and test product containing atorvastatin (10 mg) and ezetimibe (10 mg) caplsule. Both products were administered orally as a single dose separated by a one-week washout period. Atorvastatin and ezetimibe were identified and quantified using LCMS/MS for the pharmacokinetic study. The results of this investigation indicated that there were no statistically significant diffrences between the two products in either the mean concentration-time profiles or in the obtained pharmacokinetic parameters, including area under the serum concentrationtime curve concerning the relative extent of absorption, assessed by the AUC ratio (Test/Reference). The average value was found to be 1.00 ± .09 with a 90% confidence limits (CL) of 0.82-1.18. Thus, these findings clearly indicate that the two products are bioequivalent in terms of rate and extent of drug absorption.